Pelatihan Karya Tulis Ilmiah melalui Kegiatan “Workshop Riset” bagi Siswa di Kabupaten Sumenep - Kuswadi, Iwan; Asmoni, Asmoni; Fauzi, Moh; Misbahudholam AR, Muhammad (Universitas Negeri Makassar, 2024)
This training aims to measure the effectiveness of the training and mentoring program in improving the scientific writing skills of Al-Muqri Prenduan High School students. Mentoring was carried out starting with a pretest and posttest on 19 students who were selected purposively. Data were analyzed using SPSS Statistics 21 software with validity, reliability, normality and t test (paired sample test). The results of the analysis show that the instrument is valid and reliable. The normality test ensures that the data is normally distributed. The t test results showed a significant increase in students' writing abilities, with a significant difference between the pretest (77.89) and posttest (97.89) scores. Based on the results above, this training program is effective in improving students' scientific writing skills and encouraging exploration of various fields of knowledge through research and scientific writing.